Development of The Merdeka Curriculum Teaching Module based on the Local Wisdom of Bondowoso Batik - Hasanah, Rafiatul; Rasyid, Aulia Nur (Indonesian Journal of Mathematics and Natural Science Education, 2024)
The aim of this research is to develop an Merdeka curriculum teaching module for the science and science project subject matter of substances and changes based on the local wisdom of Bondowoso Batik at SMK Negeri 1 Tamanan and to find out the responses of practitioners and students to the teaching module developed. This research uses Research and Development research, with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The subjects in this research were 33 students in class X Craft Design and Production at SMK Negeri 1 Tamanan. The results of data analysis in this research show that the development of teaching modules for the Social Science Project subject based on the local wisdom of Bondowoso Batik is valid, very good, and very interesting to increase student interest. This is proven by: (1) The validation results of the material expert obtained a score of 93.84% which was included in the "Very Valid" category, (2) The validation results of the Merdeka curriculum learning planning expert obtained a score of 98.67% which received the qualification "Very Good", (3) The results of the small scale and large scale response tests obtained a score of 87.87% and 93.24% respectively which met the criteria of "Very Interesting", (4) The validation results from practitioners obtained a score of 92.66% which is included in the criteria "Very Valid. Based on these results, it can be concluded that the Merdeka curriculum teaching module based on the local wisdom of Bondowoso batik in science and science learning is suitable for use as a learning resource.